Possibilities at the end of the world - Vodovnik, Žiga (Teorija in praksa, 2024)
The article considers the thesis that today we are facing challenges that call for the invention of new principles of political, social and economic organisation. It is ever clearer that the climate crisis is not only threatening environmental and economic collapse, but above all – and it is here that the direct, yet often overlooked danger lies – our political and social collapse. The contours of the climate crisis are seen in the ongoing corrosion of the democratic political process, the erosion of political communities and the commons, and, not the least, the reliance on populist and authoritarian models to deal with the ever more dire situation. This requires a fresh look at how a new relationship can be established between life and work, production and consumption and, especially, the individual and the communal. Accordingly, in the analysis of alternatives and possibilities the article introduces a new central concept – care – as the fundamental notion and practice of the newly emerging (palliative) political and economic paradigm. We address the simple, albeit infinitely complex question: Why not use the notions of care and freedom, instead of production and consumption, as the paradigm for our new economy, which should only be a way to take care for each other?
Keywords: care; climate change; crisis; demokracija; demoracy; kriza; Podnebne spremembe; politics; politika; Politika in vladanje; skrb